2021
DOI: 10.3390/foods10112744
|View full text |Cite
|
Sign up to set email alerts
|

Yellow Mealworm and Black Soldier Fly Larvae for Feed and Food Production in Europe, with Emphasis on Iceland

Abstract: Insects are part of the diet of over 2 billion people worldwide; however, insects have not been popular in Europe, neither as food nor as a feed ingredient. This has been changing in recent years, due to increased knowledge regarding the nutritional benefits, the need for novel protein production and the low environmental impact of insects compared to conventional protein production. The purpose of this study is to give an overview of the most popular insects farmed in Europe, yellow mealworm, Tenebrio molitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 121 publications
0
39
0
Order By: Relevance
“…[71][72][73][74] The recent review outlined the economic aspects of insect farming has suggested that the interventions on upscaling mass-rearing facilities and low-value feed substrate utilization could substantially reduce operational cost. 71,75 The former has been witnessed worldwide with the establishment of industrial operators in Europe 76 and other parts. 77 The targeted production by 2030 is expected to be 50 times as high as the current level, reaching 500,000 tonnes, with 40% or 200,000 tonnes destined to aquafeed.…”
Section: Tackling the Challeng E Smentioning
confidence: 99%
“…[71][72][73][74] The recent review outlined the economic aspects of insect farming has suggested that the interventions on upscaling mass-rearing facilities and low-value feed substrate utilization could substantially reduce operational cost. 71,75 The former has been witnessed worldwide with the establishment of industrial operators in Europe 76 and other parts. 77 The targeted production by 2030 is expected to be 50 times as high as the current level, reaching 500,000 tonnes, with 40% or 200,000 tonnes destined to aquafeed.…”
Section: Tackling the Challeng E Smentioning
confidence: 99%
“…However, there are some concerns about the effect of edible insects possibly escaping into the environment and becoming invasive to natural and production systems in non-native countries. This concern is similar to that raised by Thrastardottir et al (2021) in Iceland, where an environmental risk assessment for BSF was performed before receiving a licence from the Icelandic authorities for import and trials. Their results show that BSF posed no threat to the local insect environment and that it was highly unlikely that a wild population could form if they did manage to escape, possibly because BSF is a tropical species and cannot survive in the cold climate of Iceland.…”
Section: Important Considerations When Legalising Bsfl Meal In Kenyamentioning
confidence: 66%
“…In China, 34 edible insect species, which include silkworm larvae ( Bombyx mori ), yellow mealworm ( Tenebrio molitor ), and Orthoptera species (locusts, grasshoppers, and mole crickets), have been developed and assessed for production for human consumption [ 20 ]. In Western countries, there has been a focus on developing methods to farm the house cricket ( Acheta domesticus ) and yellow mealworms for human consumption [ 18 , 21 ]. Western governments, such as the EU, have even started to recognize and regulate insect species, such as yellow mealworms, as food for humans [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, investment into developing insect farming may be necessary to increase the productivity and profitability of the insect market. In Europe, nearly 90% of the investment costs of insect farming are covered by venture capital firms in Europe [ 21 ]. In North America, startup companies, such as Aspire Food Group and All Things Bugs (GrioPro ® ), have been funded by both government and private bodies for cricket farming, for both the food and agriculture industries [ 18 ].…”
Section: Introductionmentioning
confidence: 99%